2003
DOI: 10.1016/s0149-2063_03_00079-5
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the Looking Glass: A Review of Research on Feedback-Seeking Behavior in Organizations

Abstract: This paper presents and organizes the results of two decades of research on feedback-seeking behavior according to three motives: the instrumental motive to achieve a goal, the ego-based motive to protect one's ego, and the image-based motive to enhance and protect one's image in an organization. Each motive is discussed with reference to its impact on the frequency of feedback seeking, seeking method (whether by inquiry or monitoring), timing of feedback seeking, choice of the target of feedback seeking, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
553
3
22

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(598 citation statements)
references
References 88 publications
(263 reference statements)
20
553
3
22
Order By: Relevance
“…These findings conflict with prior research that has shown a negative relationship between performance-avoid orientation and reactions to negative feedback (VandeWalle, 2003;VandeWalle et al, 2001). One potential explanation for these conflicting findings concerns differences in feedback contexts (Ashford, Blatt, & VandeWalle, 2003).…”
Section: Discussioncontrasting
confidence: 85%
“…These findings conflict with prior research that has shown a negative relationship between performance-avoid orientation and reactions to negative feedback (VandeWalle, 2003;VandeWalle et al, 2001). One potential explanation for these conflicting findings concerns differences in feedback contexts (Ashford, Blatt, & VandeWalle, 2003).…”
Section: Discussioncontrasting
confidence: 85%
“…Individuals who seek feedback should overall perform more highly (Ashford, 1986;Ashford et al, 2003). Consistent with this, in a series of studies, Morrison (1993aMorrison ( , 1993b found a positive influence of proactive information seeking on individual performance.…”
Section: Individual-level Outcomes Of Proactivitymentioning
confidence: 61%
“…Understanding what motivates such behaviors is important because these behaviors often have uncertain outcomes, and can involve image risks (Ashford, Blatt, & VandeWalle, 2003;Miller & Jablin, 1991) or ego risks (Ashford & Cummings, 1983). Proactive career behaviors also require individuals to prioritize future outcomes over short term benefits (Parker & Collins, 2009) and thus can be hard to justify in the present.…”
Section: Future Work Selves: How Salient Hoped-for Identities Motivatmentioning
confidence: 99%